Natural deep eutectic solvent-based matrix solid-phase dispersion-ultrasound assisted extraction of pesticides in pears and their determination by liquid chromatography-tandem mass spectrometry - Ana Isabel García-Valcárcel; Esther Miguel; Antonio Martín-Esteban (Advances in Sample Preparation)
In recent years, natural deep eutectic solvents (NADES) have been proposed as sustainable solvents capable of replacing the conventional harmful organic solvents typically used in sample preparation. In this regard, in this work, several NADES have been evaluated for the development of a matrix solid phase dispersion - ultrasound-assisted extraction (MSPD-UAE) method for selected pesticides (thiamethoxam, thiacloprid, pirimicarb, acetamiprid and tebuconazole) from pear (peel and pulp) samples and final determination by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Among the different NADES and dispersants tested, the one consisting of choline chloride:1,3-propanediol in a 1:4 molar ratio combined with alumina showed the best performance. The effect of the amount of dispersant, the volume of NADES, the temperature of the ultrasonic bath and the duration of sonication was then optimised using response surface methodology (RSM) based on a four-factor, three-level Box-Behnken design. Under optimal conditions, no matrix effect was observed and quantitative recoveries, ranging from 78.5 to 120 % with relative standard deviations (RSDs) lower than 20 % were obtained, reaching limits of quantification within the range 4–10 ng g-1, depending upon the analyte. In addition, after evaluation by Analytical Greenness Metric for Sample Preparation (AGREEprep), Sample Preparation Metric of Sustainability (SPMS) and Blue Applicability Grade Index (BAGI) metrics tools, the proposed method was found to be superior to other published methods in terms of safety and environmental impact with good applicability potential.